Analysis of the Use of Domino Cards in Improving Mathematics Learning Outcomes for Grade V at SDN 1 Nata - Cahyati, Cuci; Fauzi, Azra; Wardatunnissa, Yeni (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to analyze the effectiveness of using domino card media to improve the mathematics learning outcomes of fifth-grade students at SDN 1 Nata. The research background is based on the students’ low understanding of multiplication concepts and the lack of engaging instructional methods. A quantitative approach with a quasi-experimental method was employed, involving two groups: an experimental group using domino cards and a control group using conventional teaching methods. Instruments included pretest and posttest assessments and student activity observation sheets. The results showed that the use of domino cards increased the average student score from 52 to 80, while the control group only reached 60. Additionally, students in the experimental group demonstrated active participation, collaboration, and high enthusiasm during the learning process. These findings suggest that domino card media is effective in enhancing students’ mathematics learning outcomes and can serve as an innovative alternative in elementary school instruction.